The Impact of Environmental, Firm, and Relational Factors on Entrepreneurs' Ethically Suspect Behaviors. (7th January 2013) - Khan, Shaji A.; Tang, Jintong; Zhu, Renhong
Abstract : Entrepreneurs' engagement in ethically suspect behaviors (ESBs) can have seriously negative business and social consequences. Yet what defines entrepreneurs' ESBs remains unclear. Further, little is known about what factors contribute to such behaviors. This study provides conceptual clarification of entrepreneurs' ESBs and examines environmental, firm, and individual factors in relation to them. Results, based on data from 158 Chinese entrepreneurs, indicate that dynamism, firm performance, and relational social capital are all negatively related to ESBs. Firm performance partially mediates the relationship between dynamism and ESBs, and albeit with marginal support, the relationship between entrepreneurs' relational social capital and their ESBs.